Medieval bling: the display of jewellery on women's funerary monuments from England in the fourteenth and fifteenth centuries - Pam Walker (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2023)
This article suggests that more detailed analysis must be done when using artistic sources, in particular, funerary monuments, as evidence for medieval dress. Using archaeological, documentary, and literary evidence for jewellery in England in the fourteenth and fifteenth centuries, it asks why what seems to be a popular accessory was very rarely depicted on sculpted effigies and monumental brasses. Assumptions from just the visual evidence would conclude that brooches in particular were not a common piece of jewellery for noble women, but this does not correspond with the material evidence. The focus of this article, therefore, is on using an interdisciplinary approach to look at monuments as a source in their own right rather than as just a general mirror of contemporary fashion. By looking at three case studies, the article shows that deeper analysis of specific monuments can put them into religious, political, and historical context and provide information about the women depicted on them and the significance of accessories, such as brooches.